HEART AND AGE (PART I): AGEING THEORIES AND MORPHOLOGICAL CHANGES - D. U. Akasheva; I. D. Strazhesko; E. N. Dudinskaya; E. V. Naydenko; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика)
Heart ageing is a complex process including multiple cellular and molecular-level changes and resulting in different ageing phenotypes within the same biological species. According to the existing ageing theories, the multiple interacting mechanisms of ageing include somatic mutations, telomere shortening, oxidative stress, and mitochondrial defects. The review presents the most accepted ageing theories and discusses morphological characteristics of heart ageing on subcellular, cellular, and organ levels.